The role of heparanase in pulmonary cell recruitment in response to an allergic but not non-allergic stimulus. - Abigail Morris; Bo Wang; Ida Waern; Radhakrishnan Venkatasamy; Clive Page; Eric P Schmidt; Sara Wernersson; Jin-Ping Li; Domenico Spina (PLoS ONE)
Heparanase is an endo-β-glucuronidase that specifically cleaves heparan sulfate proteoglycans in the extracellular matrix. Expression of this enzyme is increased in several pathological conditions including inflammation. We have investigated the role of heparanase in pulmonary inflammation in the context of allergic and non-allergic pulmonary cell recruitment using heparanase knockout (Hpa-/-) mice as a model. Following local delivery of LPS or zymosan, no significant difference was found in the recruitment of neutrophils to the lung between Hpa-/- and wild type (WT) control. Similarly neutrophil recruitment was not inhibited in WT mice treated with a heparanase inhibitor. However, in allergic inflammatory models, Hpa-/- mice displayed a significantly reduced eosinophil (but not neutrophil) recruitment to the airways and this was also associated with a reduction in allergen-induced bronchial hyperresponsiveness, indicating that heparanase expression is associated with allergic reactions. This was further demonstrated by pharmacological treatment with a heparanase inhibitor in the WT allergic mice. Examination of lung specimens from patients with different severity of chronic obstructive pulmonary disease (COPD) found increased heparanase expression. Thus, it is established that heparanase contributes to allergen-induced eosinophil recruitment to the lung and could provide a novel therapeutic target for the development of anti-inflammatory drugs for the treatment of asthma and other allergic diseases.